Association between plasma tau and postoperative delirium incidence and severity: a prospective observational study. (February 2021) - Ballweg, Tyler; White, Marissa; Parker, Margaret; Casey, Cameron; Bo, Amber; Farahbakhsh, Zahra; Kayser, Austin; Blair, Alexander; Lindroth, Heidi; Pearce, Robert A.; Blennow, Kaj; Zetterberg, Henrik; et al.
Abstract: Background: Postoperative delirium is associated with increases in the neuronal injury biomarker, neurofilament light (NfL). Here we tested whether two other biomarkers, glial fibrillary acidic protein (GFAP) and tau, are associated with postoperative delirium. Methods: A total of 114 surgical patients were recruited into two prospective biomarker cohort studies with assessment of delirium severity and incidence. Plasma samples were sent for biomarker analysis including tau, NfL, and GFAP, and a panel of 10 cytokines. We determined a priori to adjust for interleukin-8 (IL-8), a marker of inflammation, when assessing associations between biomarkers and delirium incidence and severity. Results: GFAP concentrations showed no relationship to delirium. The change in tau from preoperative concentrations to postoperative Day 1 was greater in patients with postoperative delirium ( P <0.001) and correlated with delirium severity (ρ=0.39, P <0.001). The change in tau correlated with increases in IL-8 ( P <0.001) and IL-10 ( P =0.0029). Linear regression showed that the relevant clinical predictors of tau changes were age ( P =0.037), prior stroke/transient ischaemic attack ( P =0.001), and surgical blood loss ( P <0.001). After adjusting for age, sex, preoperative cognition, and change in IL-8, tau remained significantly associated with delirium severity ( P =0.026). Using linear mixed effect models, only tau (not NfL or IL-8) predicted recovery from delirium ( P <0.001). Conclusions: The change in plasma tau was associated with delirium incidence and severity, and resolved over time in parallel with delirium features. The impact of this putative perioperative neuronal injury biomarker on long-term cognition merits further investigation. Clinical trial registration: NCT02926417 and NCT03124303 .